THE ROLE AND FUNCTION OF MANAGEMENT IN GLOBAL ORGANIZATIONS - Hazimi Bimaruci Hazrati Havidz; Suprapto, Eko (Dinasti Publisher, 2021)
Management is an activity that exists within the organization or company in order to achieve the goals and ideals of the organization by working together with the people and resources owned by the company. Management is an activity that connects one activity to another. Activities carried out in management do not only manage people who work in the company, but include the planning, organizing, leading, and controlling processes carried out to determine and achieve organizational goals through the use of existing resources. This writing aims to find out how the role of management in organizations in the era of globalization. Because in running management it is very important to take into account the business steps that will be taken. By taking into account the steps to be taken, the company can solve problems optimally so that the company is able to continue its survival in overcoming problems and competition in this era of globalization properly and effectively.